Harnessing Energy of a Treadmill for Push-Off Assistance During Walking: In-Silico Feasibility Study - Tomc, Matej; Matjačić, Zlatko (Frontiers in Bioengineering and Biotechnology, 2022)
Regaining efficient push-off is a crucial step in restitution of walking ability in impaired individuals. Inspired by the elastic nature of ankle plantarflexor muscle-tendon complex, we propose a novel rehabilitation device: Ankle Exoskeleton using Treadmill Actuation for Push-off assistance (AN-EXTRA-Push). Using a brake and an elastic tendon, it harnesses energy of a moving treadmill during stance phase, then releases it during push-off to aid with plantarflexion torque generation. We studied the feasibility of such a device and explored some key design and control parameters. A parameter sweep of three key parameters (brake engagement timing, brake disengagement timing and elastic tendon stiffness) was conducted in-silico. Results suggest that such a device is feasible and might inherently possess some features that simplify its control. Brake engagement timing and elastic tendon stiffness values determine the level of exoskeleton assistance. Our study affirms that timing of assistive torque is crucial, especially the timing of assistance termination which is determined by brake disengagement timing. Insights acquired by this study should serve as a basis for designing an experimental device and conducting studies on effects of AN-EXTRA-Push in humans.